2010
DOI: 10.1200/jco.2009.26.2469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethnicity on Primary Treatment Choice and Mortality in Men With Prostate Cancer: Data From CaPSURE

Abstract: A B S T R A C T PurposeMen diagnosed with prostate cancer have multiple options available for treatment. Previous reports have indicated a trend of differing modalities of treatment chosen by African American and white men. We investigated the role of ethnicity in primary treatment choice and how this affected overall and cancer-specific mortality. MethodsBy utilizing data abstracted from Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE), patients were compared by ethnicity, primary treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 26 publications
11
106
1
1
Order By: Relevance
“…Researchers have also noted that strong social support may contribute to treatment patterns that influence outcomes [2]. Following progression during AS, AA men often forego RP [22] in favor of radiation or another nonsurgical therapy for PCa [23]. Such treatment patterns, together with the referral populations represented by UODB and CaPSURE sites, may explain, in part, the lower representation of AA men in our cohort.…”
Section: Discussionmentioning
confidence: 86%
“…Researchers have also noted that strong social support may contribute to treatment patterns that influence outcomes [2]. Following progression during AS, AA men often forego RP [22] in favor of radiation or another nonsurgical therapy for PCa [23]. Such treatment patterns, together with the referral populations represented by UODB and CaPSURE sites, may explain, in part, the lower representation of AA men in our cohort.…”
Section: Discussionmentioning
confidence: 86%
“…Potential risk factors and prognostic factors can be identified from these data as well [13]. In addition, they might be useful for assessment of trends in the adoption of screening, diagnostic, and treatment procedures, as well as novel technologies [54,56,58,[60][61][62][63][64][65][66][67]. For example, Vickers et al [68] demonstrated that restriction of PSA testing to only young men or selected men aged >70 yr might reduce the risk of overdiagnosis.…”
Section: 4mentioning
confidence: 99%
“…Disparities and variations in the use of imaging and treatment modalities can also be evaluated using diseasespecific registries. In particular, these databases allow examination of the relationship between baseline characteristics and the likelihood of receiving proper staging or adequate treatment [54,56,58,[60][61][62][63][64][65][66][67]. A recent CaPSURE study demonstrated substantial differences in primary treatment between African-American and white men with similar risk profiles [54].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Соглас-но исследованию CaPSURE различные методы лечения РПЖ применяли со следующей частотой: радикальная простатэктомия -54,9 %, лучевая терапия -32,1 %, андрогенная депривация -5,6 %, аблативные методы -5,3 %, активное наблюдение -2,1 % [12].…”
Section: результаты и обсуждениеunclassified